Joan Robinson and Unions, Distribution and Inflation - Williams, C. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1981)
The author examines Joan Robinson 's views on the role of unions in the modem mixed economy.